N Management of European Grasslands: Can the Exchange of Gaseous N Species Be Influenced at the Operational Level? - P. Calanca; A. Neftel; J. Fuhrer (The Scientific World Journal)
Grassland ecosystems can be regarded as biochemical reactors in which large amounts of organic nitrogen (N) are converted into inorganic N, and vice versa. If managed in a sustainable manner, grasslands should operate in a quasi steady state, characterized by an almost perfect balance between total N input and output. As a consequence, the exchange of gaseous N species (NH3, NO, NO2, N2O, and N2) between grasslands and the atmosphere is very small compared to the total N turnover. In this study, the effects of two management options (mowing and fertilization) on production and emission of nitrous oxide (N2O) from a grass/clover crop were examined on the basis of observations and model results referring to an experiment carried out on the Swiss Plateau in late summer of 2000. It was found that production and emission of N2O induced by mowing were of the same order of magnitude as those brought about by fertilization, suggesting a possible transfer of N from clover to the soil after defoliation. Emissions were strongly modulated by precipitation on time scales ranging from 1 day to 1 week. This indicates that effective control of N2O emissions through management on a day-to-day basis requires reliable medium-range weather forecasts. Model calculations were not able to reproduce essential characteristics of the emissions. The model slightly overestimated the background emissions, but severely underestimated the emission peaks following fertilizer application, and largely failed to reproduce emission induced by mowing. Shortfalls in the model used for this study were found in relation to the description of soil-water fluxes, soil organic matter, and the physiology of clover.